SISTEM INFORMASI SUPPLY CHAIN MANAGEMANT MINYAK CENGKEH PADA UD. AGUS DENGAN TEKNOLOGI WEBSITE - Gede Agus Dirtha Kristian; Suniantara, I Ketut Putu; Shofwan Hanief (Journal of Innovation Research and Knowledge, 2021)
Indonesia is an agricultural country that is rich in spices, one of which is cloves. Cloves are used as a spice for Indonesian kretek cigarettes. Besides that, the oil can also be taken from cloves. The clove oil is extracted from the flowers and leaves of cloves. UD. Agus is one of the shops that accepts the sale and purchase of clove oil, this process is done manually, namely by recording everything on paper and recapitulating it in a notebook. This process is less efficient, thus complicating the process of managing data within the company and this problem can be overcome by implementing Supply Chain Management in business processes implemented at UD. Agus, combined with implementation in an information technology. The technology applied is an information system with website technology, which is a technology that has a wide reach and is easily accessible by the internet network. This research was conducted following the flow of the Waterfall Method. The result of this research is a website-based Supply Chain Management information system. Based on the process of working and testing the system with the Blackbox Testing method, it can be concluded that the functions of the system are already running well. So that the system is suitable for use as an information system for Clove Oil Supply Chain Management at UD. Agus.